Sustainable Waste Management Improves the Quality of Industrial RDF Production and Benefits the Environments - Rapepat Sumethchotimetha; Kanokporn Sompornpailin (Current Applied Science and Technology, 2025)
Waste management significantly influences environmental conditions and living standards. This research examined raw material wastes derived from different waste managements: pre-treatment of municipal solid waste (MSW) and landfill solid waste (LSW) recovery, along with their potential effects on the quality of refuse-derived fuel (RDF), to determine an appropriate management system. Waste samples from the Eastern region of Thailand were gathered and categorized according to their source and quality. The two sample groups exhibited similarities in waste classification but differed in quantity of waste components. MSW displayed a slightly elevated average moisture and contaminant level relative to LSW. MSW had a larger fraction of soft plastics (58.78% w/w) compared to recycled landfill waste (36.55% w/w). Hard plastics represented a minor segment in both categories, yet their quantity in recycled landfill waste exceeded that in household waste by over onefold. Notably, LSW generally demonstrated superior quality compared to MSW. Both sources of solid waste were processed for RDF production in industrial operations. The RDF3 produced from the process represented 45-55% of the input raw material. The average heating value (HHV/GCV) of the RDF3 was ascertained to be 4786.90±144.10 kcal/kg. These RDF3 exhibited an average moisture content of 26.20±1.65%. The average chlorine content recorded throughout the experiment was 0.79±0.23%. Raw materials from both origins are essential for maintaining industrial production processes. RDF facility performance, when optimized, can contribute to landfill space minimization and environmental pollution mitigation. Effective management of raw materials and waste segregation provides a viable alternative fuel source for domestic industries.
Keywords: Recycling and Waste Management Techniques